2022
DOI: 10.1007/s00018-022-04136-1
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 expression in the human choroid plexus

Abstract: The choroid plexus (CP) consists of specialized ependymal cells and underlying blood vessels and stroma producing the bulk of the cerebrospinal fluid (CSF). CP epithelial cells are considered the site of the internal blood-cerebrospinal fluid barrier, show epithelial characteristics (basal lamina, tight junctions), and express aquaporin-1 (AQP1) apically. In this study, we analyzed the expression of aquaporins in the human CP using immunofluorescence and qPCR. As previously reported, AQP1 was expressed apicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(59 reference statements)
2
1
0
Order By: Relevance
“…When this analysis was performed in aged animals, the increase in ventricular size was further enlarged in the wt and AQP1 −/− animals but not in the AQP4 −/− mice, indicating the participation of AQP4 upregulation in the hydrocephalus associated with hypoxia and aging. Recently published experimental studies (107) have demonstrated an increase in AQP4 expression with aging [118]. Several findings from our study are consistent with hypoxia-induced hydrocephalus in aged animals [115,120], similar to the main symptoms of iNPH.…”
Section: Abnormal Aquaporin Expression Might Be Associated With the O...supporting
confidence: 91%
See 1 more Smart Citation
“…When this analysis was performed in aged animals, the increase in ventricular size was further enlarged in the wt and AQP1 −/− animals but not in the AQP4 −/− mice, indicating the participation of AQP4 upregulation in the hydrocephalus associated with hypoxia and aging. Recently published experimental studies (107) have demonstrated an increase in AQP4 expression with aging [118]. Several findings from our study are consistent with hypoxia-induced hydrocephalus in aged animals [115,120], similar to the main symptoms of iNPH.…”
Section: Abnormal Aquaporin Expression Might Be Associated With the O...supporting
confidence: 91%
“…In situ hybridization and western blot analysis [116,117] has shown the presence of AQP4 in choroidal plexus cells, and our recent results also confirm (using various strategies including AQP4 immunofluorescence) AQP4 expression in the secretory epithelium [96,115]. In the human choroid plexus, recent studies by Deffner et al [118] confirmed the presence of AQP4 expression in samples obtained from elder donors. The authors hypothesized that AQP4 expression in choroid plexus cells was caused by age-related changes.…”
Section: Abnormal Aquaporin Expression Might Be Associated With the O...supporting
confidence: 87%
“…The inset schematic diagram depicts the transition from the CP to the ventricle lining ependyma in a cross‐section at a level indicated by the white line. The distribution of water channels, as recently reported for the human CP (Deffner et al., 2022), is also shown. C , histological section of the CP and ependymal attachment of the lateral ventricle stained for AQP1 (green) and AQP4 (red).…”
Section: Introductionsupporting
confidence: 77%
“…First, we found that in the human brain AQP4 was not restricted to ECs but also occurred in the CP epithelium (Fig. 1; Deffner et al., 2022). This immunofluorescence finding was confirmed at the mRNA level by qPCR and at the ultrastructural level by the detection of so‐called orthogonal arrays of particles known to contain AQP4 (Rash et al., 1998; Wolburg et al., 2011).…”
Section: Introductionmentioning
confidence: 81%
“…16 For example, aquaporin-4 (AQP4), a predominant water-selective transporter that contributes to brain water dynamics, is expressed on the human ChP epithelium but mainly detected in the ependymal and subependymal regions of mice. 17 Current developments of three-dimensional (3D) in vitro models, such as inverted Transwell systems and stem cellderived ChP organoids, advance studies of functional and systemic responses of the BCSFB. [18][19][20] However, existing cultured cell models still fail to reconstitute the in vivo-like fluidic microenvironment, which will limit their utility and translation to the patients.…”
Section: Introductionmentioning
confidence: 99%